The equality of rights and responsibilities of men and women in Islam - Abd Rahman, Saodah (2019)
Islam is a religion which defends the rights and privileges of women. Before the emergence of Islam, women did not have the freedom to question their rights and privileges . Islam defends the rights and privileges of women through the reformation (al-islah) of culture , legislation as well the system of life of the jahiliyyah (period before Islam) society. The jahiliyyah tradition and system which were unjust and unethical towards women were abolished and replaced with a comprehensive Islamic tradition and laws. Islam maintains the jahiliyyah tradition which does not contradict the Islamic laws and system. The inappropriate values in the jahiliyyah system are changed by substituting and enhancing the culture according to Islamic values. Values which are against Islamic teaching and moral values are completely eliminated and replaced with Islamic values. Islam provides women with rights and privileges based on social and cultural integration along with a sound legislative system guided by the Qur’ an and Sunnah. Among the many privileges of women acknowledged by Islam as a result of reformation (al-islah) of the tradition and system of life based on the Islamic laws and systems are the recognition of the status and dignity of women as special creatures of Allah; acknowledgement of gender equality and the responsibilities of women towards their religion, society and nation; the right of women in inheritance; protection and justice towards female orphanage; recognition the status of women in marriage; limitation on the number of wives in polygamy and justice towards wives; declaration of the right of women in seeking knowledge; and recognition of the freedom of women to voice their discontent for the betterment of their own selves and justice. Islam also recognizes the superiority of women in spirituality and religion. As a result of the reformation of culture and system of life of the jahiliyyah society, Islam has successfully shown to the world that it is a religion which is concerned about the affairs of women. Misinterpretation in translating and understanding of verses of the Qur’an and Hadith, and the influence of the culture which is bound by the patriarchal system are main factors that cause the rights of women to be abandoned. Thus, it is very important for the Muslim society in the modern world to study and ponder the glorious history of Muslim women during the time of Prophet Muhammad and during their peak era of Islamic civilization in order to uphold the rights and privileges of women.